Vprašanje vizualizacije abstraktnih bitij v slovenski slovstveni folklori - Stanonik, Marija (Traditiones (Ljubljana), 2001)
Despite the fact that the initial starting point of this paper is whole empirical, the results obtained by the comparative research method might also possess theoretical value. The paper tries to find answers to the following questions: What are the possibilities of visualization of those folklore motifs which cannot be verified by experience, and which are inaccessible to one's eyes and ears in the course of everyday life? How does the Slovene literary folklore transform such events into words? How does it depict and illustrate various apparitions and mystical creaturs, and how these beings represented in Slovene art? What are the advantages of employing modern audiovisual technicques in dealing with this subject?
Keywords: ethnology; etnologija; slovstvena folklora; vizualna kultura; Slovenia; Slovenija